2013
DOI: 10.1177/0957650913495537
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of near surge instabilities onset in a turbocharger compressor

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…If the flow pushed downstream by the impeller does not have enough flow momentum to overcome the pressure gradient in the di↵user, the flow direction is reversed at the impeller discharge and a tip leakage over the compressor blades establishes. The occurrence of such a flow reversal during o↵-design operating conditions at the outer periphery of the impeller is in agreement with the observations by Despres et al [10] using numerical flow simulations to investigate a di↵erent geometry. The tip leakage recirculations are increased towards lower mass-flow rates and lead to a distorted swirling flow at the inlet of the compressor, which result in a reduced performance of the impeller.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…If the flow pushed downstream by the impeller does not have enough flow momentum to overcome the pressure gradient in the di↵user, the flow direction is reversed at the impeller discharge and a tip leakage over the compressor blades establishes. The occurrence of such a flow reversal during o↵-design operating conditions at the outer periphery of the impeller is in agreement with the observations by Despres et al [10] using numerical flow simulations to investigate a di↵erent geometry. The tip leakage recirculations are increased towards lower mass-flow rates and lead to a distorted swirling flow at the inlet of the compressor, which result in a reduced performance of the impeller.…”
Section: Resultssupporting
confidence: 90%
“…Unsteady RANS formulations [10], Detached Eddy Simulation (DES) [11] and the Large Eddy Simulation (LES) approach [12] have been used to describe the unsteady flow-field at o↵-design operating conditions. Unsteady RANS resolves the integral scales in a turbulent flow-field while all smaller flow scales are modelled.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, compressor speed plays a role in the onset of whoosh noise, as indicated by Evans and Ward [3]. In fact, Després et al [32] did not found any rotating stall at an operating point close to surge but at low compressor speed. Experimental inlet spectra at high frequency range ( Fig.…”
Section: Compressor Acoustic Spectramentioning
confidence: 93%
“…Stall is more intense at the suction side (SS) of the main blades, which indicates that splitter blades should be closer to main blade pressure side (PS) rather than being a midpitch distance. Després et al [32] also noted that passages corresponding to main blade PS deliver more flow than channels which are delimited by the splitter blade PS for a midpitch location of the splitter blades. Moreover, Jeon [36] noted that, in a centrifugal fan, splitter blades located near main blade PS produce less overall SPL than the same impeller with splitter placed at a different pitchwise position.…”
Section: Flow Field Investigationmentioning
confidence: 99%
“…The deviations in the spectra of the sensors forming duct arrays can be contributed to the three-dimensional effects caused by duct modes and the propagation of flow instability due to the operation of the compressor near surge. The deviation among the spectra of the inlet duct array is primarily due to duct modes as the flow instability is reported only to propagate few diameters upstream [33,41]. Furthermore, a similar pattern is observed in the inlet spectra at design operation conditions thereby implying this to be a feature dependent on geometry rather than the flow conditions.…”
Section: Ps Open Configurationmentioning
confidence: 70%